Nagios : system and network monitoring. - Barth, Wolfgang (No Starch Press, Inc., 2009)
"Good system administrators recognize problems long before anyone asks, "Hey, is the Internet down?" Nagios, an open source system and network monitoring tool, has emerged as the most popular solution for sys admins in organizations of all sizes. It's robust but also complex, and Nagios: System and Network Monitoring, 2nd Edition, updated to address Nagios 3.0, will help you take full advantage of this program. Nagios, which runs on Linux and most *nix variants can be configured to continuously monitor network services such as SMTP, POP3, HTTP, NNTP, SSH, and FTP. lt can also supervise host resources (processor load, disk and memory usage, running processes, log files, and so on) and environmental factors, such as temperature and humidity. This book is your guide to getting the most out of this versatile and powerful monitoring tool. Inside Nagios, you'll learn how to: • Install and configure the Nagios core, all standard plugins, and selected third-party plugins • Configure the notification system to alert you of ongoing problems-and to alarm others in case of a serious crisis • Program event handlers to take automatic action when trouble occurs • Write Perl plugins to customize Nagios for your unique needs • Quickly understand your Nagios data using graphing and visualization tools • Monitor Windows servers, SAP systems, and Oracle databases. The book also includes a chapter that highlights the differences between Nagios versions 2 and 3 and gives practical migration and compatibility tips. Nagios: System and Network Monitoring, 2nd Edition is a great starting point for configuring and using Nagios in your own environment." (Copied from the back cover).